Effyekty bikvadratichnogo obmyennogo vzaimodyei{cyrillic, short}stviya v fyerromagnyetikakh Gai{cyrillic, short}zyenbyerga - Tiwari M.; Srivastava R.N. (My University, 2025)
The effects of the biquadratic-exchange interaction on magnetization and susceptibility for spin-1 systems are investigated. The simple Green's function technique using Callen-type decoupling and RPA decoupling has been utilized to obtain the spin wave energies. Spin wave dispersion has been discussed. Limitations of decoupling have been indicated. © 1980 Società Italiana di Fisica.